Perancangan Sistem Pusat Dokumentasi Arsip Rapat Terpadu (Padu) Pada Kantor Balai Penjaminan Mutu Pendidikan (BPMP) Provinsi Jambi - Metra, Pol; Putra, Hendry; Aulia, Norin Nur; Salsabila, Amanda; Julia; A’yun, Nada Qurrota; Riandityo, MHD Malzi; Oktara, Ridho; Hafidzudin, Hasan (Universitas Pahlawan Tuanku Tambusai, 2025)
This research focuses on designing an effective system for storing, managing, displaying, and facilitating the search and grouping of digital meeting archive documents. The aim is to provide an integrated and user-friendly digital platform for managing meeting archives at BPMP Jambi Province, as well as accelerating the process of searching and grouping documents based on relevant categories. The methodology used includes direct observation, informal interviews, literature review, and a User-Centered Design (UCD) approach to ensure the system meets user needs. The design result is a functional and user-friendly web-based PADU System. This system provides centralized storage, comprehensive document management features, and an intuitive interface for displaying meeting archives. Advanced search features by keyword or date, as well as the ability to group documents by type or meeting agenda, are key solutions. The implementation of the PADU System is expected to significantly increase operational efficiency, minimize the risk of losing important documents, and support digital transformation at BPMP Jambi Province towards more modern and accountable archive management.